Solution chemistry of carbonate minerals and its effects on the flotation of hematite with sodium oleate - Li, Dong; Yin, Wan-zhong; Xue, Ji-wei; Yao, Jin; Fu, Ya-feng; Liu, Qi (International journal of minerals, metallurgy and materials, 2017)
The effects of carbonate minerals（dolomite and siderite） on the flotation of hematite using sodium oleate as a collector were investigated through flotation tests, supplemented by dissolution measurements, solution chemistry calculations, zeta-potential measurements, Fourier transform infrared（FTIR） spectroscopic studies, and X-ray photoelectron spectroscopy（XPS） analyses. The results of flotation tests show that the presence of siderite or dolomite reduced the recovery of hematite and that the inhibiting effects of dolomite were stronger. Dissolution measurements, solution chemistry calculations, and flotation tests confirmed that both the cations(Ca2+ and Mg2+) and CO32+ions dissolved from dolomite depressed hematite flotation, whereas only the 23CO-ions dissolved from siderite were responsible for hematite depression. The zeta-potential, FTIR spectroscopic, and XPS analyses indicated that Ca2+, Mg2+, and CO32-（HCO3-） could adsorb onto the hematite surface, thereby hindering the adsorption of sodium oleate, which was the main reason for the inhibiting effects of carbonate minerals on hematite flotation.